Antidyslipidaemic effect of Ipomoea batatas L. extract with increased PCSK-9 levels in atherosclerotic rats - I Wayan Putu Sutirta Yasa; I Made Jawi; Agung Nova Mahendra; Putu Angga Wiradana; I Gede Widhiantara (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2026)
Atherosclerosis is the largest cause of mortality worldwide, and Low-Density Lipoprotein (LDL) is a primary risk factor for this illness. The purpose of this research was to determine the effect of purple sweet potato (Ipomoea batatas L.) extract on cholesterol, LDL, PCSK9, and MDA levels in rats fed a high-cholesterol diet. This true experimental study used a randomised pre-test-post-test control group design. Wistar rats were randomly assigned to three groups. Purple sweet potato extract (PSPE) was prepared by 24-hour maceration with 70% ethanol. All rats were fed a high-cholesterol diet for 14 days, followed by pre-test measurements of cholesterol, LDL, PCSK9, and MDA on day 15. Rats were then randomly divided into control (no treatment), PSPE (200 mg/day), and Simvastatin (0.9 mg/kg BW) groups. After one month of treatment, post-test analyses were performed for all parameters. The results showed an increase in serum cholesterol, LDL and MDA levels in rats fed a high-cholesterol diet (p<0.05) compared to the PSPE and Simvastatin groups. The high-cholesterol diet also resulted in a significant (p<0.05) decrease in PCSK9 when compared to the PSPE and Simvastatin groups. In the PSPE group there was a decrease in cholesterol, LDL, and MDA, and PSPE (p<0.05) compared to the control group. In the Simvastatin group, the increase in PCSK9 was very low compared to the PSPE group. PSPE has antidyslipidaemic activity by reducing total cholesterol status, LDL, and oxidative stress while promoting PCSK-9 function. Further research is still needed to provide a comprehensive understanding of the mechanism of action of PSPE as an antioxidant source in patients with atherosclerosis.